Hematopoietic Akt2 deficiency attenuates the progression of atherosclerosis. Issue 2 (12th November 2014) - Rodlan, Noemi; Chamorro‐Jorganes, Aránzazu; Araldi, Elisa; Wanschel, Amarylis C.; Aryal, Binod; Aranda, Juan F.; Goedeke, Leigh; Salerno, Alessandro G.; Ramírez, Cristina M.; Sessa, William C.; Suárez, Yajaira; Fernández‐Hernando, Carlos
ABSTRACT: Atherosclerosis is the major cause of death and disability in diabetic and obese subjects with insulin resistance. Akt2, a phosphoinositide‐dependent serine‐threonine protein kinase, is highly express in insulin‐responsive tissues; however, its role during the progression of atherosclerosis remains unknown. Thus, we aimed to investigate the contribution of Akt2 during the progression of atherosclerosis. We found that germ‐line Akt2‐ deficient mice develop similar atherosclerotic plaques as wild‐type mice despite higher plasma lipids and glucose levels. It is noteworthy that transplantation of bone marrow cells isolated from Akt2 ‐/‐ mice to Ldlr ‐/‐ mice results in marked reduction of the progression of atherosclerosis compared with Ldlr ‐/‐ mice transplanted with wild‐type bone marrow cells. In vitro studies indicate that Akt2 is required for macrophage migration in response to proatherogenic cytokines (monocyte chemotactic protein‐1 and macrophage colony‐stimulating factor). Moreover, Akt2 ‐/‐ macrophages accumulate less cholesterol and have an alternative activated or M2‐type phenotype when stimulated with proinflammatory cytokines. Together, these results provide evidence that macrophage Akt2 regulates migration, the inflammatory response and cholesterol metabolism and suggest that targeting Akt2 in macrophages might be beneficial for treating atherosclerosis.—Rodlan, N., Chamorro‐Jorganes, A., Araldi, E., Wanschel, A. C., Aryal, B., Aranda, J. F., Goedeke, L., Salerno, A. G., Ramírez, C. M., Sessa, W. C., Suárez, Y., Fernández‐Hernando, C. Hematopoietic Akt2 deficiency attenuates the progression of atherosclerosis. FASEB J . 29, 597‐610 (2015). www.fasebj.org